Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Pemoderasi Pada Perusahaan Yang Terdaftar Di BEI Periode 2014-2018 - Helmi Prilla Aldino; Nurlaila Nurlaila (JURNAL PUNDI, 2021)
Fast traslate Icon translate This study aims to examine the effect of CSR disclosure on firm value with profitability as a moderating variable. The population in this study were all companies listed on the Indonesia Stock Exchange (IDX) in the period 2014 to 2018. Data collected by the purposive sampling method used managed regression analysis (MRA) or test interactions. The results show that CSR proxied by the size of the board of commissioners does not significantly influence the value of the company and profitability is able to strengthen the influence of CSR proxied by the size of the board of commissioners to the value of the company.